Multiple criteria decision making comparison between electre II method and deviation method - Choong, Hon Yoong. (2009)
With the development of information technology and internet services, suppliers’ information can be gathered with ease and accuracy. By analyzing these data, the requestors are able to compare all the suppliers and rank them according to their performances in the desired criterion of the requestors. With the help of Multi Criteria Decision Making methods, the suppliers’ ranking can be done easily and efficiently. However, there are a lot of methods which give different suppliers’ ranking even though they are compared based on the same data. Hence, the requestors have to choose the best ranking system so that they are able to fulfill their requirements. In this project, two methods were compared to find a suitable way to normalize the performance for ELECTRE II. ELECTRE II method started with the comparison of the concordance index and discordance index of all the suppliers, followed by the computation of outranking relationship and final ranking from best to worst whereas Deviation Method measured the difference between the supplier’s value and the requestor’s value to calculate the individual criterion score. Supplier with the highest score will be the best in the ranking. After that, ELECTRE II was compared with Deviation Method to find a more suitable and accurate suppliers’ ranking system in terms of over influence, veto power, rank completeness and rank reversal. The better suppliers’ ranking system was selected for the requestors. At the end of the project, ELECTRE II was found to be the better suppliers’ ranking system with its stronger performance in over influence and veto power.